2015
DOI: 10.1007/s40808-015-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the behavior of Vegetation Indices in the salt dome of Korsia in North-East of Darab, Fars, Iran

Abstract: The use of remote sensing for rapid and accurate evaluation of phenomena, specially land covers is very important. In this study, for modeling and estimated of salt dome was used visible atmospherically resistant index (VARI), difference vegetation index (DVI), enhanced vegetation index (EVI), green difference vegetation index (GDVI), normalized difference vegetation index (NDVI), optimized soil adjusted vegetation index (OSAVI), soil adjusted vegetation index (SAVI), infrared percentage vegetation index (IPVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 28 publications
0
12
0
2
Order By: Relevance
“…The inverse association of some indices with salinity was for the reason that most of such indices used near-infrared band. In effect, as salinity increased, the spectral value of the near-infrared band decreased [41]. Moreover, the Normalized Difference Vegetation Index had a significant negative correlation with soluble sodium, calcium, and magnesium at a 95% confidence level.…”
Section: Resultsmentioning
confidence: 90%
“…The inverse association of some indices with salinity was for the reason that most of such indices used near-infrared band. In effect, as salinity increased, the spectral value of the near-infrared band decreased [41]. Moreover, the Normalized Difference Vegetation Index had a significant negative correlation with soluble sodium, calcium, and magnesium at a 95% confidence level.…”
Section: Resultsmentioning
confidence: 90%
“…Despite this, these authors have demonstrated that low-cost UAVs may improve forest monitoring after disturbance, even in those habitats and situations where resource limitation is an issue. In general, VARI shows a minimal sensitivity to atmospheric effects [26,61,62].…”
Section: Correlations Of Vari With Vegetation Cover Using Remote Sensing Techniquesmentioning
confidence: 99%
“…Equation 1 is used to estimate the fraction of vegetation with a minimal sensitivity to atmospheric effects (Gitelson et al, 2002;Mokarram et al, 2015;Mokarram et al, 2016). The addition of blue-band data in Equation 1 is to minimize atmospheric effects (Schneider et al, 2008).…”
Section: Vegetation Index Formulasmentioning
confidence: 99%